Enhancing the Efficacy of Higher Education: Integrating Quality Assurance with Dialogic Pedagogy - Bhatta Joshi, Yashoda Kumari (Ganeshman Darpan, 2025)
The integration of quality assurance systems with dialogic pedagogy represents a critical challenge in contemporary higher education. This paper examines how universities can effectively balance institutional quality management requirements with innovative teaching practices that promote meaningful classroom dialogue. Through comprehensive analysis of secondary literature and own observations, the article demonstrates the interconnected nature of systemic quality assurance and classroom-level pedagogical effectiveness. The findings emphasize the vital role of stakeholder engagement, evidence-based approaches, and the alignment between micro-level teaching practices and macro-level educational objectives. This paper concludes enhancing both quality assurance processes and dialogue-based teaching methods, ultimately preparing students for the complexities of a rapidly evolving global milieu.